2019
DOI: 10.4102/sajhrm.v17i0.1033
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of sacrifice, workplace friendship and career concerns as explanatory mechanisms of employees’ organisational commitment

Abstract: Orientation: Employees’ psychological attachment to their organisation remains an important topic of inquiry for organisations concerned about improving their talent management practices for the purpose of retaining valuable human capital.Research purpose: The aim of the study was to explore the constructs of job-embedded sacrifice, workplace friendship and career concerns as potential underlying explanatory mechanisms of employees’ affective, continuance and normative commitment towards the organisation. Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
2
22
1
Order By: Relevance
“…However, since the mediation of compassion is uniquely positioned between organizational elements and commitment, we explain it using logical arguments. Since leadership styles, workplace friendships and a serving culture are positively associated with positive work outcomes (Coetzee et al, 2019;Liden et al, 2014; Zoghbi-Manrique-de-Lara & Viera-Armas, 2019), we replicate these positive outcomes with compassion at work.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, since the mediation of compassion is uniquely positioned between organizational elements and commitment, we explain it using logical arguments. Since leadership styles, workplace friendships and a serving culture are positively associated with positive work outcomes (Coetzee et al, 2019;Liden et al, 2014; Zoghbi-Manrique-de-Lara & Viera-Armas, 2019), we replicate these positive outcomes with compassion at work.…”
Section: Discussionmentioning
confidence: 67%
“…It is also possible in situations where individuals perceive that others care about them (Zulueta, 2016), driving knowledge sharing and team work in a trustful manner (Sias, 2005). Workplace friendship among colleagues working in healthcare organizations is important and has been found to contribute to positive outcomes (Coetzee, Ferreira, & Potgieter, 2019). Hence, workplace friendship in healthcare organizations is a critical factor of success and can also lead to some other positive attitudes at work.…”
Section: Workplace Friendship and Compassion At Workmentioning
confidence: 99%
“…Perry- Smith and Blum (2000) found that organisations that implement WLBS, such as flexible work arrangement, on-site day care and dependent care, experienced improved performance. A recent study performed by Coetzee et al (2017) showcase that organisational retention strategy that includes WLBS, such as flexible work arrangement, enhances…”
Section: Discussionmentioning
confidence: 99%
“…Deery and Jago (2015) suggest that a major determinant of effective implementation of WLBS is HR policy that affirms work-life balance culture. As such, it is the WLBS that an organisation has put in place that determines the extent of employees' satisfaction with work (SWW), commitment to work and turnover intention (Abe et al, 2018;Coetzee, Ferreira, & Potgieter, 2017). Studies have revealed that a supportive HR policy enhances the effective implementation of WLBS (Caillier, 2016, Daverth et al, 2016.…”
Section: Relationship Between Work-life Balance Strategies and Organisational Performancementioning
confidence: 99%
“…The concept of job-embedded sacrifice influencing psychological attachment and commitment to an organization (Coetzee et al, 2019) has particular relevance to physicians. Physicians are very familiar with the notion of sacrifice (Matz, 1998) and risk to one's own health is seen as part of the role (Klitzman, 2008) making it easy to get lost in the current zeitgeist where metaphors of war, martyrdom, and heroes abound.…”
Section: Returning To the Professionmentioning
confidence: 99%